Upaya Guru Pendidikan Agama Kristen Dalam Mengatasi Kesulitan Belajar Siswa - Relly Poluan; Winne Adeline Berhenti; Marthin Dani Martoyo (MAGENANG : Jurnal Teologi dan Pendidikan Kristen, 2022)
The purpose of this study is to describe how the efforts of Christian Religious Education teachers for students at Tateli Regeneration Vocational School, inhibiting factors in overcoming student learning difficulties at Tateli Regeneration Vocational School, solutions to overcome factors inhibiting student learning difficulties at Tateli Regeneration Vocational School. This research is a qualitative research using descriptive method which is carried out at the Tateli Regeneration Vocational School, Mandolang District, Minahasa Regency. 2021 calendars. Data collections, observations, interviews, studies and documents. From the results of the analysis and interpretation of the data, there are indications that: (1) PAK teachers have not fully carried out their duties as supervisors. (2) The obstacles encountered by the teacher are the attention of students, lazy to study, socializing with friends, parents who are less attentive and there is no cooperation. (3) Teachers try to carry out their obligations to educate, solve problems, guide, and provide direction so that students are able to achieve educational goals and overcome student learning difficulties.